A Review on Studies Conducted on Justice-Based Outpatient Services (Outpatient’s Times of Visit) - Mojtaba Hosseini, Seyed; Malmir, Razieh; Maher, Ali; Raeyat Mohtashami, Abolfazl (International Journal of Engineering and Technology, 2018)
Justice in health is a serious and important challenge throughout the world. Use of health & treatment services based on need is the most appropriate method to measure justice in health & treatment sector. Use of health services can be measured by the rate of visits for such services. Outpatient's visits are particularly a valuable scale for better understanding of justice-based use of health services as well as to explain regional differences.All convenient sources were included in the paper using key words. The sources have been published in Persian and English languages.Researches indicated that studies conducted in developing countries are very extensive. Some injustices in use of health services are seen either in Iran or other countries. There is no standard for times of visits. The time of visits is recorded consistently in advanced countries which is ignored in Iran. The studies are conducted in advanced countries to change doctors' views but there are no such studies in Iran.The studies of justice-based use of health services should be conducted annually to evaluate the rate of justice growth in healthcare system. Furthermore, referral registration system is necessary to conduct better studies. As a result, it is very essential to change habits of public and doctors' view thus to reduce health costs.Â Â